2S2P1D Model Calibration Error from User Panel for One Bitumen and One Bituminous Mixture. (26th May 2019) - Mangiafico, S.; Sauzéat, C.; Di Benedetto, H.
Abstract : The objective of this study is to analyse the differences between experimental LVE properties of both a straight-run bitumen and a bituminous mixture and simulations with analogical 2S2P1D (2 Springs, 2 Parabolic elements, and 1 Dashpot) model fitted by 14 different users. Data for the bitumen consisted of isotherms ofG ∗ andφ obtained from DSR complex modulus tests at 12 different temperatures ranging from −29.9°C to 60.0°C and frequencies ranging from 6.3 to 40 Hz, for a total of 60 data points. Data for the bituminous mixture consisted of isotherms ofE ∗ andφ obtained from strain-controlled traction/compression complex modulus tests at 8 different temperatures ranging from −29.7°C to 38.8°C and frequencies ranging from 0.01 to 10 Hz, for a total of 55 data points. All users worked independently and for the same time duration of one hour to fit the 2S2P1D model on both sets of data. Successful simulations of experimental data of both bitumen and mixture were generally obtained by all the users over the whole range of frequencies and temperatures, regardless of their familiarity and experience with the model. The accuracy of the model to fit experimental data is all the more evident if the great spans of complex modulus (G ∗ of the bitumen between 10 −2 and 10 3 MPa, E ∗ of the mixture between 10 and 40000 MPa) are considered. The obtained results highlight the convenience of 2S2P1D model to perform multiscale modelling of LVE behaviour of bituminous materials, from bitumens to mixtures.